Global Vaccine Update. Issue 3 (May 2023) - Callister, Lynn Clark
Abstract : Vaccine administration has decreased globally, making more children at greater risk for vaccine preventable diseases. Our global health and nursing expert, Dr. Callister, explains the situation and what can be done to promote more wide-spread vaccination of the world population as recommended by the World Health Organization.